Clinical, hormonal, and radiological characteristics of patients with sellar mass at a neurosurgical unit of a neuro-specialized hospital in Dhaka (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Background: Mass in the sellar region represents a diverse group of tumors with variable clinical manifestations, hormone secretion patterns and radiological appearance.Objective: To assess the preoperative clinical, hormonal, and radiological characteristics of sellar mass patients preparing for surgery.Methods: This cross-sectional study included 150 patients [83 female, 67 male; median age 35 (interquartile range 28-45) years] with sellar mass identified by magnetic resonance imaging (MRI) of the brain in pituitary protocol & admitted to the neurosurgical unit of a neuro-specialized hospital in Dhaka from January 2019- September 2022. Demographic data, clinical manifestations, and preoperative hormonal and radiological test results were obtained from face-to-face interviews, clinical examinations, and medical records with prior approval from the ethics committee and maintaining strict confidentialityResults: Non-pituitary sellar masses were observed in 19% of study participant; craniopharyngioma (12%) and meningioma (6%) were the most common. Non-functioning pituitary macroadenoma (58%) predominated among the pituitary lesions. Among the hormone-secreting tumors, 13% had growth hormone and 5% each had prolactin and ACTH-secreting tumor. The majority of the participants had presenting symptoms due to the pressure effect of sellar mass, specifically headache (83%) and visual disturbance (80%). Secondary hormonal deficiency was present in 111 (74%) participants. Among them, 54 (36.0%) had secondary hypoadrenalism, 26 (17.3%) had secondary hypothyroidism and 71 (47.3%) had secondary hypogonadism. None had preoperative diabetes insipidus. The diameter of tumors was 3 cm (2.2-4.1) (median and IQR), whereas 44 (29.3%) had giant tumors (diameter ≥4 cm). A suprasellar and parasellar extension was present in 112 (74.7%) and 52 (34.7%) patients respectively.Conclusions: Non-functioning pituitary tumors presenting with mass effects were the most frequent cause of sellar mass in patients preparing for surgery. Hypopituitarism was frequent and involved different axes including adrenal, thyroid and gonad. The masses were fairly large and a considerable proportion had an extension to supra and parasellar areas.J Assoc Clin Endocrinol Diabetol Bangladesh, January 2023; 2 (1): 14-18